First record of the invasive exotic sap beetle Phenolia (Lasiodites) picta (Coleoptera: Nitidulidae) in Greece - Kalaentzis, Konstantinos; Mpamnaras, Athanasios Georgiou; Kazilas, Christos (ENTOMOLOGIA HELLENICA, 2020)
The exotic sap beetle Phenolia (Lasiodites) picta (Macleay, 1825) is recorded for the first time in Greece. In August 2018, a nitidulid beetle was found and photographed near Mt. Pelion of Central Greece. It was later identified as P. picta, a recent alien species in Europe, previously recorded from Spain, France, and Turkey. Photographic material and information on the species’ distribution, biology, and potential economic and ecological implications are discussed.